Primary neoplasms of the heart. Clinical and histological presentation of 50 cases - Fernandes,Fábio (2001)
OBJECTIVE: To analyze clinical and histologic findings of 50 patients with primary neoplams of the heart in a tertiary referral center. METHODS: From 1980 to 1998, we retrospectively analyzed 50 patients, 32 of whom were females, whose ages ranged from 9 to 73 years (mean age = 44.16±18 years). RESULTS: Most tumors were located in the left side of the heart (72%), myxoma being the most common (84%) histologic type. The other histologic types found were as follows: fibroma (4%), lipoma (2%), rhabdomyosarcoma (2%), hemangioma (2%), sarcoma (2%), angiosarcoma (2%), and lymphoma (2%). Diagnosis was established by echocardiography in 94% of the cases. Clinical findings were as follows: dyspnea (36%), weight loss (20%), palpitations (18%), chest pain (16%), fever (8%), and arthralgia (6%). All patients with thromboembolic phenomena (10%) had left atrial myxoma. Approximately 20% of the patients were asymptomatic at the initial clinical assessment. CONCLUSION: Primary cardiac tumors are a rare entity with diverse clinical and histologic findings, requiring, therefore, a high level of clinical suspicion.